2002
DOI: 10.1128/cdli.9.4.777-783.2002
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 Induces Acute Biphasic Reduction in the Levels of Circulating Leukocytes in Mice

Abstract: We investigated the acute hematological changes caused by interleukin-18 (IL-18) in mice. Intraperitoneal administration of IL-18 (2 g/mouse) resulted in biphasic decreases in the number of leukocytes in the blood. The first phase of decrease occurred within 2 h of IL-18 administration and was followed by a transient increase at 5 h. The second phase of decrease occurred at around 6 h, reaching a nadir which lasted for more than 24 h. In mice deficient in inducible nitric oxide (NO) synthase, the first phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Increased survival is accompanied by decreased levels of IFN-g and MIP-2 in anti-IL-18-treated animals challenged with E. coli LPS, whereas IFN-g and TNF-a concentrations are decreased in treated mice challenged with S. typhimurium. This is consistent with a finding that injections of IL-18 into mice result in profound neutropenia [87]. In mice primed with heatkilled P. acnes, a neutralizing antibody to IL-18 completely prevented LPS-induced hepatic damage, which was associated with reduced IFN-g, TNF-a, and Fas ligand levels, whereas a neutralizing antibody to IL-12 had no effect [88].…”
Section: Role Of Il-18 In Sepsissupporting
confidence: 90%
“…Increased survival is accompanied by decreased levels of IFN-g and MIP-2 in anti-IL-18-treated animals challenged with E. coli LPS, whereas IFN-g and TNF-a concentrations are decreased in treated mice challenged with S. typhimurium. This is consistent with a finding that injections of IL-18 into mice result in profound neutropenia [87]. In mice primed with heatkilled P. acnes, a neutralizing antibody to IL-18 completely prevented LPS-induced hepatic damage, which was associated with reduced IFN-g, TNF-a, and Fas ligand levels, whereas a neutralizing antibody to IL-12 had no effect [88].…”
Section: Role Of Il-18 In Sepsissupporting
confidence: 90%
“…We previously found that a single administration of IL-18 induced NO in peripheral blood in mice (20). The present study shows that plasma NO metabolites, as well as pancreatic iNOS gene expression, were significantly increased after the initiation of AP and that these levels were significantly lower in IL-18 KO than in WT mice.…”
Section: Discussionmentioning
confidence: 48%
“…Upregulation of natural killer cell-mediated cytotoxicity (17), induction of Fas ligand (18), and development of type 1 T-helper (Th1) cells (19) are the first major actions. Additionally, our recent study showed that injection of IL-18 as a bolus into the peritoneal cavity of mice dramatically increased nitric oxide (NO) in peripheral blood, reaching a peak at 4 h, then decreasing to a supranormal level by 24 h (20). NO is a key mediator in modulating microcirculatory change and…”
Section: Introductionmentioning
confidence: 98%
“…On the one hand IL-18 leads to release of TNF alpha, IL-6, and other chemokines, but on the other hand it increases NO level in peripheral blood, as was observed in experimental study [38]. Some studies show that NO may have a protective effect by increasing pancreatic microvascular blood flow [39,40].…”
Section: Discussionmentioning
confidence: 91%